Applied groundwater modeling simulation of flow and advective transport - Anderson, Mary P. | Woessner, William W. (Academic Press / New York, 1992)
Contents: equations and numerical methods; The conceptual model and grid design; Boundaries; Sources and sinks; Profile models; Special needs for transient simulations; Model execution and the calibration process; Documenting and reporting your modeling study; Postaudists; How good predictions; Practicle tracking of groundwater flow advective transport of contaminants